EVALUATION OF SOME PHYSICO-CHEMICAL PARAMETERS OF THE TIN CAN ISLAND CREEK, LAGOS, NIGERIA. - AGARIN, O. J; DAVIES, I. C.; ONYEMA, I. C. (Nigerian Journal of Fisheries, 2019)
The anthropogenic impact on coastal waters has increased due to activities and increasing population around the coastal environments. The physico-chemistry parameters of the Tincan Island creek were investigated for five (5) months (May to September, 2018) at three stations. The parameters were determined using standard ecological analytic procedures. PAST and SPSS were used for the statistical analysis. Some physicochemical parameters showed monthly variations linked with flood water inflow and tidal lagoon water incursion. These include rainfall, air temperature (25.2-33ºC), water temperature (27-31ºC), salinity (2-18‰), pH (5.94-7.33), total dissolved solid (1569.20-15189mg/L), conductivity (2760-24900μS/cm), turbidity (2.72-39.20NTU), dissolved oxygen (0.36- 5.12mg/L), biochemical oxygen demand (3-211mg/L), chemical oxygen demand (12-1769mg/L), nitrate-nitrogen (1.7-4.83mg/L), phosphate-phosphorus (0.03-6.29mg/L) and sulphate (19.1-1177.7mg/L). Most of the recorded parameters from this study were found fluctuating with season and were not within acceptable limit of tolerance as recommended by WHO. The presence study showed that the Tincan Island creek is an organically polluted environment which might lead to significant alteration of the water chemistry if nothing is done on time. This finding would help environmentalist and other agencies to regulate activities such as indiscriminate disposal of waste around the creek.